Breast Cancer Metastasis to Pituitary Infandibulum - Poursadegh Fard, Maryam (Shiraz University of Medical Sciences, 2011)
Metastasis from breast cancer to other parts of the body is very common, but the spread of the tumor to pituitary gland, especially to infandibulum, is a rare presentation. At the time of pituitary metastasis, a majority of the patients have clinical and radiological evidence of the disease. It seems that the posterior area of the gland is the most common site of metastasis, probably due to highly rich blood supply through the hypophyseal artery. The present report introduces a case of a 55-years-old woman presented with diabetes insipidus resulting from metastasis of the tumor to pituitary infandibulum, which is a rare site for metastasis, without significant complaint resulting from metastasis to other part of the body, or other primary diseases. Further evaluation revealed that in spite of previous reports, which metastasis usually happens in end stage of cancer, the patients had primary breast cancer. In subsequent evaluations of the case, hypofunction of adenohypophysis was also detected.